ICP22 and the UL13 Protein Kinase Are both Required for Herpes Simplex Virus-Induced Modification of the Large Subunit of RNA Polymerase II - Long, Melissa C. (American Society for Microbiology, 1999)
Herpes simplex virus type 1 (HSV-1) infection alters the phosphorylation of the large subunit of RNA polymerase II (RNAP II), resulting in the depletion of the hypophosphorylated and hyperphosphorylated forms of this polypeptide (known as IIa and IIo, respectively) and induction of a novel, alternatively phosphorylated form (designated IIi). We previously showed that the HSV-1 immediate-early protein ICP22 is involved in this phenomenon, since induction of IIi and depletion of IIa are deficient in cells infected with 22/n199, an HSV-1 ICP22 nonsense mutant (S. A. Rice, M. C. Long, V. Lam, P. A. Schaffer, and C. A. Spencer, J. Virol. 69:5550–5559, 1995). However, depletion of IIo still occurs in 22/n199-infected cells. This suggests either that another viral gene product affects the RNAP II large subunit or that the truncated ICP22 polypeptide encoded by 22/n199 retains residual activity which leads to IIo depletion. To distinguish between these possibilities, we engineered an HSV-1 ICP22 null mutant, d22-lacZ, and compared it to 22/n199. The two mutants are indistinguishable in their effects on the RNAP II large subunit, suggesting that an additional viral gene product is involved in altering RNAP II. Two candidates are UL13, a protein kinase which has been implicated in ICP22 phosphorylation, and the virion host shutoff (Vhs) factor, the expression of which is positively regulated by ICP22 and UL13. To test whether UL13 is involved, a UL13-deficient viral mutant, d13-lacZ, was engineered. This mutant was defective in IIi induction and IIa depletion, displaying a phenotype very similar to that of d22-lacZ. In contrast, a Vhs mutant had effects that were indistinguishable from wild-type HSV-1. Therefore, UL13 but not the Vhs function plays a role in modifying the RNAP II large subunit. To study the potential role of UL13 in viral transcription, we carried out nuclear run-on transcription analyses in infected human embryonic lung cells. Infections with either UL13 or ICP22 mutants led to significantly reduced amounts of viral genome transcription at late times after infection. Together, our results suggest that ICP22 and UL13 are involved in a common pathway that alters RNAP II phosphorylation and that in some cell lines this change promotes viral late transcription.